Performance and emission characteristics of a stationary diesel engine fuelled by Schleichera Oleosa Oil Methyl Ester (SOME) produced through hydrodynamic cavitation process - Ashok Kumar Yadav; M. Emran Khan; Amit Pal; Uttam Ghosh (Egyptian Journal of Petroleum)
In this study, the performance and emission characteristics of biodiesel blends of 10, 20, 30 and 50% from Schleichera Oleosa oil based on hydrodynamic cavitation were compared to diesel fuel, and found to be acceptable according to the EN 14214 and ASTM D 6751 standards. The tests have been performed using a single cylinder four stroke diesel engine at different loading condition with the blended fuel at the rated speed of 1500 rpm. SOME (Schleichera Oleosa Oil Methyl Ester) blended with diesel in proportions of 10%, 20%, 30% and 50% by volume and pure diesel was used as fuel. Engine performance (specific fuel consumption and brake thermal efficiency) and exhaust emission (CO, CO2 and NOx) were measured to evaluate the behaviour of the diesel engine running on biodiesel. The results show that the brake thermal efficiency of diesel is higher and brake specific fuel consumption is lower at all loads followed by blends of SOME and diesel. The performance parameter for B10, B20, B30 and B50 were also closer to diesel and the CO emission was found to be lesser than diesel while there was a slight increase in the CO2 and NOx. SOME produced by using hydrodynamic cavitation seems to be efficient, time saving and industrially viable. The experimental results revel that SOME-diesel blends up to 50% (v/v) can be used in a diesel engine without modifications. Keywords: Performance, Emission, Diesel engine, Schleichera Oleosa Oil, Biodiesel hydrodynamic cavitation (HC)